Compact bioreactor treatment system for malaysian municipal sewage - Kutty, S.R.M. (Nova Science Publishers, Inc., 2015)
Integrated bioreactor called "Compact extended aeration reactor" (CEAR) was developed to perform biological wastewater treatment. Synthetic sample was used to imitate the municipal sewage during the experiment. The treatment units are integrated in series within a single concentric setup. The objective is to achieve wastewater treatment within a small footprint that can accomplish the stringent effluent discharge limits of nitrogen imposed in Malaysia. Conversely, to also realize a prospective target aimed at augmented profit margin for the developers, through leverage in extra space from land recovery. The recirculation of thickened activated sludge (RAS) from clarifier was carried out to maintain the concentration of biomass in the bioreactor and return of residual nitrate that could be discharged untreated. Internal recirculation (IR) was operated for the nitrate transfer to pre-anoxic chambers for the purpose of denitrification. This chapter covers removal efficiencies of organic matter, nitrogen and total suspended solids within a small footprint bioreactor. The benchmarking of the effluent discharge is according to Malaysia regulatory standards. The system of treatment process follows denitrification taking place both pre-anoxic and post-anoxic chambers, combined nitrification and organic removal in the aeration chamber, and clarifier settling the biomass prior to discharge. Sludge was wasted daily in order to maintain the solids retention time and avoiding excess growth of biomass in the system. The bioreactor used suspended growth process, extended aeration with longer solids retention time, and anoxic conditions to achieve the desired goals. This chapter also investigated the effectiveness of total nitrogen (TN) removal, by operating combinations of different IR ratios through variable influent nitrogen concentrations. The bioreactor effluent values have conformed to Department of Environment (DOE) Malaysia's 2009 revised. Â© 2015 by Nova Science Publishers, Inc. All rights reserved.